Antihypertensive and tóxica activities of methanolic extract of Calceolaria myriophylla “zapatilla” in mice with hypertension induced by L-NAME - Condorhuamán, Martin (2017)
Objective of this experimental study was to determine the antihypertensive and toxic activities of methanolic extract from Calceolaria myriophylla (zapatilla). Male albino mice Mus musculus BALB/c of two months, 25±5 g weigth, were used for induction of hypertension with N-nitro-L-arginine methyl ester (L-NAME) administered at doses of 130 mg/kg/day, orally for seven days, measuring baseline and post induction blood pressure. The mice were divided into six groups of ten animals: negative control (distilled water), positive control (L-NAME), experimental groups at doses of 200, 400 and 600 mg/kg of methanolic extract, and enalapril group to doses 75 mg/kg. The treatment was administered for 30 days continuous and blood pressure was measured every five days. The study of chronic toxicity was determined to repeated doses for 60 days in normotensive rats, divided into three groups of six animals each group; using doses of 400 and 600 mg/kg. The methanolic extract from Calceolaria myriophylla presented abundance of phenolics compounds, better antihypertensive effect at the dose of 600 mg/kg compared with enalapril and it did not show chronic toxicity at the doses evaluated; concluding that the methanolic extract showed antihypertensive activity without toxic effects.